Factors that facilitate Registered Nurses in their first‐line nurse manager role. (27th June 2013) - Cziraki, Karen; McKey, Colleen; Peachey, Gladys; Baxter, Pamela; Flaherty, Brenda
<x xml:space="preserve">Abstract</x> Aim To determine the factors that attract and retain Registered Nurses in the first‐line nurse manager role. Background The first‐line nurse manger role is pivotal in health‐care organisations. National demographics suggest that Canada will face a first‐line nurse manager shortage because of retirement in the next decade. Determination of factors that attract and retain Registered Nurses will assist organisations and policy makers to employ strategies to address this shortage. Methods The study used an exploratory, descriptive qualitative approach, consisting of semi‐structured individual interviews with 11 Registered Nurses in first‐line nurse manager roles. Results The findings revealed a discrepancy between the factors that attract and retain Registered Nurses in the first‐line nurse manager role, underscored the importance of the mentor role and confirmed the challenges encountered by first‐line nurse managers practicing in the current health‐care environment. Conclusions The first‐line nurse manager role has been under studied. Further research is warranted to understand which strategies are most effective in supporting first‐line nurse managers. Implications for Nursing Management Strategies to support nurses in the first‐line nurse manager role are discussed for the individual, programme, organisation and health‐care system/policy levels.